Dithieno[3,2-b:2′,3′-d]phospholes: A Look Back at the First Decade - Romero-Nieto, Carlos; Baumgartner, Thomas (Synlett, 2013)
In this account, we describe our efforts in developing the chemistry of the highly luminescent dithieno[3,2-b:2′,3′-d]phosphole system over the last ten years. We provide an overview of the synthetic possibilities and the inherent tunability of the emission properties offered by this particular heterole.1 Introduction2 Synthesis and Properties of Dithieno[3,2-b:2′,3′-d]phospholes3 Functionalization of Dithieno[3,2-b:2′,3′-d]phospholes3.1 Phosphorus Functionalization3.2 Functionalization at the 2- and 6-Positions3.2.1 Symmetric Functionalization3.2.2 Asymmetric Functionalization3.3 Incorporation of Fused Rings onto the Main Scaffold4 Photophysical Properties5 Conclusions
Keywords: phosphorus; heterocycles; chromophores; polycycles; substituent effects; chemoselectivity.